Foreign investment and dispute resolution law and practice in Asia - Bath, Vivienne; Nottage, Luke.; T&F eBooks (Abingdon, Oxon : Routledge, 2011)
"This book considers foreign investment flows in major Asian economies. It critically assesses the patterns and issues involved in the substantive law and policy environment which impact on investment flows, as well as the related dispute resolution law and practice. The book combines insights from international law and comparative study and is attentive to the socio-economic contexts and competing theories of the role of law in Asia. Contributions come from both academics with considerable practical expertise and legal practitioners with strong academic backgrounds. The chapters analyze the law and practice of investment treaties and FDI regimes in Asia looking specifically at developments in Japan, India, China, Indonesia, Malaysia, Korea and Vietnam. The book explores the impact of the Asian Financial Crisis in the late 1990s and the Global Financial Crisis a decade later, examining actual trends and policy debates relating to FDI and capital flows in Asia before and after those upheavals.Foreign Investment and Dispute Resolution: Law and Practice in Asia is a valuable resource for practitioners, academics and students of International and Comparative Law, Business and Finance Law, Business, Finance and Asian Studies"--
1. Foreign investment and dispute resolution law and practice in Asia : an overview / Vivienne Bath and Luke Nottage -- 2. Investment arbitration in Asia : five perspectives on law and practice / Luke Nottage and J. Romesh Weeramantry -- 3. A passive player in international investment law : typically Japanese? / Shotaro Hamamoto -- 4. The quandary for Chinese regulators : controlling the flow of investment into and out of China / Vivienne Bath -- 5. Chinese investment treaties : a procedural perspective / Nils Eliasson -- 6. Foreign investment in Indonesia : the problem of legal uncertainty / Simon Butt -- 7. The Japan-Indonesia economic partnership agreement : an energy security perspective / Sita Sitaresmi -- 8. Foreign investment laws and the role of FDI in Malaysia's 'new' economic model / Salim Farrar -- 9. Treaty definitions of 'investment' and the role of economic development : a critical analysis of the Malaysian historical Salvors case / Govert Coppens -- 10. The 'object and purpose' of Indian international investment agreements : failing to balance investment protection and regulatory power / Prabhash Ranjan -- 11. The evolution of Korea's modern investment treaties and investor-state dispute settlement provisions / Joongi Kim -- 12. Legal issues in Vietnam's FDI law : protections under domestic law, bilateral investment treaties and sovereign guarantees / Hop Dang -- 13. Review of Asian views on foreign investment law / M. Sornarajah.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Investments, Foreign -- Law and legislation -- Asia; Dispute resolution (Law) -- Asia; Electronic books